Hubungan Antara Konsep Diri dengan Kemampuan Komunikasi Interpersonal - Arizona Arizona; Ahmad Hikami; Ramtia Darma Putri (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2021)
Self-concept is an individual's perception of the physical, social, and psychological mind. A positive self-concept will motivate individuals to always think positively and act positively. Interpersonal communication is determined by personal self-concept, because someone with a positive self-concept will be open and confident with the surrounding environment. Based on this description, the researcher wants to find out that (1) what is the description of self-concept in the eighthgrade students of SMP Seri Tanjung in the academic year 2020/2021? (2) what is the description of interpersonal communication in the eighth grade students of SMP Seri Tanjung in the academic year 2020/2021? and (3) what is the correlation between self-concept and interpersonal communication in the eighth grade students. The population of this study was all students of Eighth Gradeat SMP Seri Tanjung for the Academic Year 2020/2021 as many as 86 students divided into 3 classes. There are two variables, namely self-concept as the independent variable and students' interpersonal communication as the dependent variable. Data is taken with a psychological scale. The data obtained were analyzed using correlation analysis. The results of the percentage descriptive analysis showed that the self-concept the students of SMP Seri Tanjung was included in the medium criteria with a percentage of 70%, while students' interpersonal communication was also in the medium category with a percentage of 80%. The two variables have a positive correlation of 0.747 which explains that the relationship between self-concept and interpersonal communication has a positive value, which means there is a relationship between self-concept and interpersonal communication of eighth grade students at SMP Seri Tanjung.